Trimodal Therapy vs. Radical Cystectomy for Muscle-Invasive Bladder Cancer: A Meta-Analysis - Ding, Hui; Fan, Ning; Ning, Zhongyun; Ma, Deyuan (Frontiers in Oncology, 2020)
Background: To compare the difference between trimodal therapy (TMT) and radical cystectomy (RC) in treating muscle-invasive bladder cancer, we performed a meta-analysis for data from the following database. Methods: We searched PubMed, Chinese biomedicine literature database, the Cochrane Library, China National Knowledge Internet databases, Wanfang databases, and Google Scholar up to December 2019. The main outcome measures assessed were overall survival (OS), cancer-specific survival (CSS), mortality, and Charlson comorbidity score (CCS). Two authors independently evaluated the study quality and extracted data. All data were analyzed using Review Manager (version 5.3). Results: After database retrieval, article selection, data extraction, and quality assessment, nine articles comprising 5,721 cases from the TMT group and 48,262 cases from the RC group were included in this study. The data showed that there was no statistical difference between TMT and RC at <10 years OS [pooled hazard ratio (HR) = 1.26, 95% confidence interval (CI): 0.92–1.73, Z = 1.46, P = 0.14], while OS of the RC group was higher than that of the TMT group at more than 10 years (pooled HR = 1.34, 95% CI: 1.18–1.54, Z = 4.33, P < 0.0001). As for CSS, compared with the TMT group, the patients in the RC group had longer CSS (pooled HR = 1.50, 95% CI: 1.29–1.76, Z = 5.15, P < 0.00001). Compared with RC, TMT is linked to an obvious increase in all-cause mortality and bladder-specific cancer mortality (pooled HR = 1.30, 95% CI: 1.16–1.46, Z = 4.55, P < 0.00001; pooled HR = 1.32, 95% CI: 1.15–1.51, Z = 3.92, P < 0.0001). The bladder cancer patients belonging to CCS “0” score preferred RC [pooled relative risk (OR) = 0.94, 95% CI: 0.89–0.98, Z = 2.79, P = 0.005], while CCS “2” score's patients were prone to TMT (pooled OR = 1.40, 95% CI: 1.29–1.53, Z = 7.73, P < 0.00001). Conclusions: Overall, this meta-analysis suggests that the efficacy of TMT is non-inferior to that of RC at <10-year OS, and RC is superior to TMT at more than 10-year OS. Therefore, TMT may be a reasonable treatment option in well-selected patients who are unsuitable for surgery or are not willing to experience surgery. In the future, more high-quality, large-sample randomized controlled trials (RCTs) are needed to verify the results.